2016
DOI: 10.3171/2016.2.spine151039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reliability and validity of the newer AOSpine subaxial cervical injury classification (C-3 to C-7)

Abstract: OBJECTIVE The authors evaluated a new classification for subaxial cervical spine trauma (SCST) recently proposed by the AOSpine group based on morphological criteria obtained using CT imaging. METHODS Patients with SCST treated at the authors’ institution according to the Subaxial Cervical Spine Injury Classification system were included. Five different blinded researchers classified patients’ injuries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 23 publications
2
30
0
1
Order By: Relevance
“…During the second assessment, the expert group demonstrated significantly higher values than those using the A-F, Harris, and Argenson classification systems, a finding in accordance with data reported in current literature. 5,9,11 The main disadvantages of the AOS scale as reported by the raters included (1) a challenging identification of F1 and F2 fractures, (2) common confusion between A2 and A4 types in vertically split vertebral injuries, and (3) a frequent absence of facet-joint trauma classification in addition to the major injury. The intraobserver kappa was found to be higher for the AOS scale than for the Argenson system in our study and reached a moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…During the second assessment, the expert group demonstrated significantly higher values than those using the A-F, Harris, and Argenson classification systems, a finding in accordance with data reported in current literature. 5,9,11 The main disadvantages of the AOS scale as reported by the raters included (1) a challenging identification of F1 and F2 fractures, (2) common confusion between A2 and A4 types in vertically split vertebral injuries, and (3) a frequent absence of facet-joint trauma classification in addition to the major injury. The intraobserver kappa was found to be higher for the AOS scale than for the Argenson system in our study and reached a moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…The two most popular classification systems for cervical spine injury are the AOspine classification and SLIC systems [1,[4][5]. These systems provide a means to classify injuries into diagnostic categories based on injury pattern (AOspine) and also allow for guidance regarding operative versus non-operative management (SLIC).…”
Section: Discussionmentioning
confidence: 99%
“…While several classification systems exist, subaxial spine injuries are broadly defined as fractures, dislocations, or ligamentous disruption of the C3 to C7 vertebral levels. Many of these injuries can lead to cervical spine instability and SCI [4][5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, they concluded that this classification system is reliable and reproducible [25]. On the contrary, however, a study by Silva et al found B type injuries and classification of facet injuries to be unreliable with low intraobserver and interobserver reliabilities [26]. Overall, this classification system may prove more reliable to reproducible than the SLIC; however, there may be difficulty with agreement across intermediate fractures and those affecting the facet.…”
Section: Aospine Subaxial Cervical Spine Injury Classificationmentioning
confidence: 95%